Muscular activity during uphill cycling: Effect of slope, posture, hand grip position and constrained bicycle lateral sways - Duc, S.; Bertucci, W.; Pernin, J. N.; Grappe, F. (Journal of Electromyography and Kinesiology, 2008)
Despite the wide use of surface electromyography (EMG) to study pedalling movement, there is a paucity of data concerning the muscular activity during uphill cycling, notably in standing posture. The aim of this study was to investigate the muscular activity of eight lower limb muscles and four upper limb muscles across various laboratory pedalling exercises which simulated uphill cycling conditions. Ten trained cyclists rode at 80% of their maximal aerobic power on an inclined motorised treadmill (4%, 7% and 10%) with using two pedalling postures (seated and standing). Two additional rides were made in standing at 4% slope to test the effect of the change of the hand grip position (from brake levers to the drops of the handlebar), and the influence of the lateral sways of the bicycle. For this last goal, the bicycle was fixed on a stationary ergometer to prevent the lean of the bicycle side-to-side. EMG was recorded from M. gluteus maximus (GM), M. vastus medialis (VM), M. rectus femoris (RF), M. biceps femoris (BF), M. semimembranosus (SM), M. gastrocnemius medialis (GAS), M. soleus (SOL), M. tibialis anterior (TA), M. biceps brachii (BB), M. triceps brachii (TB), M. rectus abdominis (RA) and M. erector spinae (ES). Unlike the slope, the change of pedalling posture in uphill cycling had a significant effect on the EMG activity, except for the three muscles crossing the ankle`s joint (GAS, SOL and TA). Intensity and duration of GM, VM, RF, BF, BB, TA, RA and ES activity were greater in standing while SM activity showed a slight decrease. In standing, global activity of upper limb was higher when the hand grip position was changed from brake level to the drops, but lower when the lateral sways of the bicycle were constrained. These results seem to be related to (1) the increase of the peak pedal force, (2) the change of the hip and knee joint moments, (3) the need to stabilize pelvic in reference with removing the saddle support, and (4) the shift of the mass centre forward.